Evaluation of ‘Stop Smoking in its Tracks’: an intensive smoking cessation program for pregnant Aboriginal women incorporating contingency-based financial rewards - Megan E Passey; Janelle M Stirling (Public Health Research & Practice, 2018)
Background: Smoking during pregnancy is three times as common among Aboriginal women as non-Aboriginal women, with consequent higher rates of adverse health outcomes. Effective interventions to support Aboriginal women to quit smoking have not yet been identified.